The Effect of Dividend Policy, Profitability, and Liquidity on Company Value at PT. Gudang Garam Tbk on the Indonesia Stock Exchange - Kambuno S., Ronaldo; Halik, Johannes Baptista; Jaya, Amir (Master of Management Study Program, Universitas Kristen Indonesia Paulus, 2025)
This study discusses how dividend policy, profitability, and liquidity policies affect company value. The entire consolidated financial statements of PT Gudang Garam Tbk from 2014 to 2023 are included in the population being studied. The balance sheet and income statement of PT Gudang Garam Tbk were taken at the same time using a purposive sampling method. Classical assumption tests and multiple regression analysis were used for secondary data. The research shows that dividend policy, liquidity, and profitability simultaneously influence company value. The coefficient of determination (R²) has a value of 0.76, indicating that liquidity, dividend policy, and profitability affect company value by 76%. Other variables not examined in this study account for the remaining 24%..